Spatial analysis of rainfall daily trends and concentration in Chile - Sarricolea Espinoza, Pablo Andrés; Martín-Vide, Javier (Investigaciones Geográficas: Una mirada desde el sur, 2014)
Chile has a great diversity of climates. In average, the rainfall differs between 0.7 mm (Iquique, North) and 1,814.8 mm (Valdivia, South) according to the main meteorological stations. The small rainfall amount in the North concentrates on few days, with only 3 days per year. In Central Chile, there are among 16 to 42 rainy days and in the South more than 150 days. In order to understand the correlation between precipitation totals (grouped into 1-mm size classes) and the number of rain days, climatologists use the Concentration Index (CI). In the present study, this index was calculated for 17 meteorological stations across Chile for the period between 1965-2005, also using other indicators: Coefficient of Variation, Temporal irregularity and the relation of precipitation with teleconnections. The results of the CI show a high variation among the regions (from 0.51 to 0.76). The highest one was recorded in La Serena (30º S), with values higher than 0.70. From La Serena, the CI decreases gradually, reaching values of about 0.60 in the Atacama Region (North) and further South in the Biobío Region. The concentration of rainfall has increased in the last sub-period (1985-2005), as inter-seasonal variability.